Investigating the Adoption of Telemedicine Services: An Empirical Study of Factors Influencing Physicians’ Perspective in Pakistan - Kamal, S. A; Hussain, S.; Shafiq, M.; Jahanzaib, M. (The Nucleus, 2018)
Â Telemedicine services are increasingly becoming an integral part of health care system of many countries around the globe. However, despite its emergent proliferation its acceptance hasnâ€™t been strikingly popular in clinical settings of developing countries, where shortage of practicing medical professionals is prevalent. The objective of this research study is to develop a theoretical model based on Technology Acceptance Model (TAM) and then empirically testing it for determining the key factors influencing doctorsâ€™ intention to adopt and use Telemedicine Services in clinical settings of a developing country. The partial least square model obtained from data of 220 doctors reflects that Perceived Usefulness (Î² = 0.30) and Perceived Ease of Use (Î² = 0.26), are the most significant drivers for doctors to use Telemedicine services in their practice, confirming the validity of original TAM constructs. In addition, new predictive constructs including Legal and Ethical Concerns ((Î² = -0.23) and Response Cost (Î² = -0.15) are found to have significant negative effects on usage intention of doctors. The survey findings reflect that telemedicine services are still in its infancy in Pakistan. Rigorous awareness and training programs are required to increase its acceptance among medical professionals. Effective financial and legal solutions also need to be devised leading physicians to uptake the adoption of telemedicine service.